A comparative analysis of modern trends in carsharing: with reference to Kazakhstan (Journal of Mathematics Mechanics and Computer Science, 2022)
This article presents the results of a systematic literature review on modern trends in the implementation of car-sharing and conducts a comparative analysis of Kazakhstani carsharing solutions to some of the world’s most popular alternatives. The findings reveal some socio-economic and cultural barriers for adopting and promoting carsharing services by studying the results of recent literature. It also considers business models and features of various car-sharing services and suggests a P2P(peer-to-peer) model as the main model of the proposed carsharing system, a system architecture of which is presented as well. The main contribution of this article to the research topic is analyzing existing carsharing solutions both in Kazakhstan and abroad, identifying the gaps in the development of carsharing in the country, suggesting the preferred business model, system architecture and finding directions for future research.
Keywords: carsharing; sustainability; carbon emissions; shared mobility; sharing economy